Penentuan Hidrokuinon dalam Sampel Krim Pemutih Wajah secara Voltammetri Menggunakan Screen Printed Carbon Electrode (SPCE) - Ani Mulyasuryani; Alfita Savitri (Jurnal Kimia Valensi, 2015)
Hydroquinone in whitening face cream has been banned since 2008, but is still found facial bleaching creams containing hydroquinone. Therefore, in this study have been developed voltammetric method for the determination hydroquinone in face whitening cream. This study has been carried out optimization of pH and measurement conditions. Optimizationof pH has been done in cyclic voltammetry, while the optimization of measurement carried out by differential pulse voltammetry. In this study, using a screen printed carbon electrode with a three electrode system. The results showed that the increase in pH causes a decrease in the anodic peak potential (Epa) of hydroquinone. The optimum conditions resulted at pH 2 in which the anodic current (Ipa) is the highest. The optimum condition resulted at high pulse 200 mV and scan rate at 15 mV/sec. The linear regression concentration is 1-100 μM, limit of detection is 0.015 μM and sensitivity is 0.0652 μM/µA. The results showed that the concentration of hydroquinone in the face whitening cream samples ranged from 0 to 0.02%DOI :http://dx.doi.org/10.15408/jkv.v0i0.3145.